How the situation in the trading sector affects retail trade turnover in Russian regions - Tsvetkov, Valery A.; Abramov, Egor G.; Mayorova, Elena A. (Economy of Regions, 2025)
Understanding the mechanisms of the trading sector’s influence on retail trade turnover in the regions is necessary to improve its regulation and reduce regional disparities in consumption. The objective of the research was to identify indicators characterizing the situation in the trading sector in Russian regions, which have the greatest impact on retail trade turnover and explain its regional disparities. Based on the analysis of regional statistics for 2018–2022, a machine learning model was created. In this model, the average per capita retail trade turnover was chosen as the dependent variable, and seven indicators of the situation in the trading sector and the average monetary income per capita were chosen as independent variables. In order to assess the impact of each factor, the constructed model is interpreted with the help of the feature_importances_ attribute and the SHAP framework. As a result, it was confirmed that trade throughout the Russian Federation is efficient enough to satisfy consumer demand. However, it is not the main factor determining regional disparities in sales: income is such a factor. It was found that the share of Internet sales in turnover was the most important indicators of the situation in the trading sector. E-commerce is the most promising form of trade. Thus, the creation of comfortable conditions for its development will reduce regional disparities in consumption. The share of commercial networks has a large but ambiguous impact on regional sales imbalances. The regulation of commercial network activities is one of the key aspects of state regulation of trade, where a balance should be provided. This balance ensures the maximum socio-economic effect of network trade, while at the same time curbing its excessive spread. The number of retail outlets was also important in terms of its impact on retail trade turnover. The results of the research create conditions for improving the tools of trade regulation in order to better satisfy the needs of the population for consumer goods throughout the Russian Federation. Further research will include the development of improved mechanisms for the regulation of e-commerce.